Análise eletrocardiográfica e da variabilidade da frequência cardíaca materna, fetal e neonatal em bovinos da raça holandesa variedade preto e branco - Quevedo, Dario Alejandro Cedeño [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Stress can interfere with animal welfare, as well as generate cardiovascular, endocrine and metabolic disorders in cows and fetuses during the transition period and neonatal phase, known as adjustment period, phase changes necessary to adapt to extrauterine life. Therefore, the study was design to describe the electrocardiographic parameters (ECG), the normal range of heart rate (HR), the indices of heart rate variability (HRV) and the association with endocrine and biochemical profiles of Holstein pregnant cow, her fetus and neonate. The study was designed to evaluate the physiological changes during the adaptation period and in cows during the transition period between three weeks before and after delivery. The evaluations were done into the group of neonates between female and male and in pre and post-delivery cows for ECG. In time domain, heart rate (HR), beat-to-beat interval (RR), the square root of variance of RR intervals (SDNN), and square root of the mean squared differences of successive RR intervals (RMSSD) were assessed. The studied parameters of frequency domain were, low frequency measured in normalized units (LF nu), high frequency measured in normalized units (HF nu), and LF/HF ratio. Glucose, magnesium, potassium, phosphorus, calcium, sodium and cortisol concentrations in plasma were determined. The ECG data revealed that during the first month of life, no differences were observed in P, Q, S and T waves, in PR, QRS, and ST intervals and in axis orientation. There was a significant difference in R amplitude and duration in the QT interval. Among sexes, the difference was in the Q amplitude. In the fetal stage, an increase in low frequency (LF nu) and a decrease in high frequency (HF nu) and the SDNN index to birth was recorded, this reflects a shift toward dominance of the sympathetic nervous system. Cows in the transition period, the SDNN and the ratio LF / HF displayed a significant ...

O estresse pode interferir no bem-estar animal, assim como gerar alterações cardiovasculares, endócrinas e metabólicas em vacas e fetos durante no período de transição e na fase neonatal, conhecida como período de adaptação, fase de mudanças necessárias para adaptar-se à vida extrauterina. Por conseguinte, o estúdio foi desenhado para descrever o comportamento dos parâmetros eletrocardiográficos (ECG), dos valores normais da frequência cardíaca (FC), dos índices de variabilidade da frequência cardíaca (VFC) e a sua associação com os perfis endócrinos e bioquímicos da vaca prenhe da raça Holandesa variedade preto e branco, assim como do feto e do recém-nascido. Para o ECG, as avaliações foram realizadas no grupo de recém-nascidos separados por sexo, e no grupo das vacas, separadas por período pré-parto e pós-parto. No domínio do tempo, mediu-se, a frequência cardíaca (FC), intervalo entre batimentos (RR), desvio-padrão da média de todos os intervalos RR normais (SDNN), raiz quadrada da média do quadrado das diferenças entre intervalos RR normais adjacentes (RMSSD). No domínio da frequência (por análise FFT) calculou-se a potência normalizada da banda LF (LF normal) e da banda de HF (HF normal), bem como o quociente LF / HF. Foram analisados glicose, magnésio, fósforo, cálcio, sódio e cortisol. Os dados de ECG revelaram que, durante o primeiro mês de vida, não houve diferença nas ondas P, Q, S e T, em intervalos PR, QRS, e ST e na orientação do eixo. Houve uma diferença significativa em amplitude e duração R no intervalo QT. Entre os sexos, a diferença estava na amplitude Q. Foram registrados no estágio fetal, aumento da baixa frequência (LF nu), diminuição da alta frequência (HF nu) bem como no índice SDNN até o nascimento, o que reflete mudança em direção à predominância do sistema nervoso simpático. Em vacas, os índices SDNN e LF/HF...
Maternal, fetal and neonatal electrocardiographic and heart rate variability assessment in Holstein cattle
Keywords: Neonatologia; Eletrocardiografia; Variabilidade do batimento cardíaco; Bovino - Reprodução; Holandês (Bovino); Cattle - Reproduction